1989
DOI: 10.1093/jnci/81.21.1655
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Expansion of Tumor-Derived Activated Cells for Therapeutic Use

Abstract: We obtained tumor specimens from patients with cancer in an effort to activate and expand the tumor-infiltrating lymphocytes for therapeutic use. With the use of finely minced tumor preparations from eight different tumor types, recombinant interleukin-2, and lymphokine-activated killer cell-conditioned medium, lymphocytes were expanded in vitro. After 4 weeks, the tumor cells were virtually absent from the cultures. At this point, the lymphocytes were termed "tumor-derived activated cells" (TDACs). Over 90% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Cell fines BRXBrl, BRXBr2, and BRXBr4 were used for the induction and screening of monoclonal antibodies for use in antibody-drug conjugate therapy. Cell lines BRXBr5, BRXBr6X, and BRXBr7 have been utilized in the induction and characterization of tumor-derived activated cells (TDAC) [4]. For this therapeutic approach, tumor mince was cultured in medium containing IL-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell fines BRXBrl, BRXBr2, and BRXBr4 were used for the induction and screening of monoclonal antibodies for use in antibody-drug conjugate therapy. Cell lines BRXBr5, BRXBr6X, and BRXBr7 have been utilized in the induction and characterization of tumor-derived activated cells (TDAC) [4]. For this therapeutic approach, tumor mince was cultured in medium containing IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…As the tumor cells in the lymphocyte cultures were killed, tumor cells were added back to stimulate the cell-killing specificity and expansion of the lymphocytes. Cultured tumor cells have served this purpose [4] for TDAC of breast cancer, and for several other types of cancer, such that cultured cells may replace the requirement for biopsy tumor cells in the development of TDAC cultures. As a result of successful tumor cell culture, the possibility of TDAC therapy can be extended to a greater number of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary assessment of growth response showed that two classes of mammary gland effector steroids, estrogen and progesterone, had no significant influence on growth of these cell lines in cul- [15,25] chromium release assay. 51Cr-labeled BT20 cells (2.5 × 103) were incubated with varying numbers of lymphocytes in the presence of I p~g/ml heteroconjugate antibody [26].…”
Section: Discussionmentioning
confidence: 97%
“…Tumor-derived activated lymphocyte cultures were prepared from previously cryopreserved tumor minces incubated with r-IL2 as described [15]. Briefly, lymphocytes (5 x 105 cells/ml) were grown in medium containing 10% human serum and 1000 U/ml r-IL2.…”
Section: Methodsmentioning
confidence: 99%